3/7 (3 over 7) cannot be simplified nor can 4/7 (4 over 7)
3 over 7
(3/14) / (4/7) = (3/14) * (7/4) = (3*7)/(14*4) = (3*1)/(2*4) = 3/8
3 4/7 minus 1/7 is 3 3/7
(-7/12) / (-3/4) = (7/12) / (3/4) = (7/12) * (4/3) = (7/3)*(1/3) = 7/9
7
4/7 x 3/4 is 3/7
3/7 (3 over 7) cannot be simplified nor can 4/7 (4 over 7)
4/7 + 3/7 = 1
3 over 7
(3/14) / (4/7) = (3/14) * (7/4) = (3*7)/(14*4) = (3*1)/(2*4) = 3/8
3 4/7 minus 1/7 is 3 3/7
(-7/12) / (-3/4) = (7/12) / (3/4) = (7/12) * (4/3) = (7/3)*(1/3) = 7/9
7/8 / 3/4= 7/8 x 4/3== 7/6
3/4 + 3/7 = 33/28
(4/3)*(6/7) = 8/7
4/7 minus 3/4 is -5/28